Implementation of Generalized Model Predictive Control Algorithm for DC-DC Boost Converter on STM32 - Hmidene, Ali; Bennasr, Hichem; M'sahli, Faouzi (Electrica, 2024)
Abstract This paper presents the practical implementation of a Generalized Model Predictive Control (GPC) algorithm using low-cost microcontrollers. The computational efficiency of the predictive controller is achieved through an explicit analytical solution calculated offline. The proposed approach is implemented, reviewed, and compared with academic benchmarks and complex dynamic systems. Experimental results are provided using both Black-Box and White-Box models based on a boost converter, with a comparison between the two models. The algorithm demonstrates good control performance with low computational time, making it suitable for real-time applications in systems with fast dynamics. Cite this article as: A. Hmidene, H. Bennasr and F. M'sahli, "Implementation of generalized model predictive control algorithm for DC-DC boost converter on STM32," Electrica, 24(3), 722-732, 2024.